2023
DOI: 10.1093/plcell/koad057
|View full text |Cite
|
Sign up to set email alerts
|

PHOSPHATE STARVATION RESPONSE1 (PHR1) interacts with JASMONATE ZIM-DOMAIN (JAZ) and MYC2 to modulate phosphate deficiency-induced jasmonate signaling in Arabidopsis

Abstract: Phosphorus (P) is a macronutrient necessary for plant growth and development. Inorganic phosphate (Pi) deficiency modulates the signaling pathway of the phytohormone jasmonate in Arabidopsis thaliana, but the underlying molecular mechanism currently remains elusive. Here, we confirmed that jasmonate signaling was enhanced under low Pi conditions, and the CORONATINE INSENSITIVE1 (COI1)-mediated pathway is critical for this process. A mechanistic investigation revealed that several JASMONATE ZIM-DOMAIN (JAZ) rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 158 publications
0
29
0
Order By: Relevance
“…The p-value for each comparison between the two data sets is displayed above the asterisk. The experiments were repeated three times with similar results.process of jasmonate-induced anthocyanin synthesis along with its homologs AtPHL1, AtPHL2, and AtPHL3(He et al, 2023). Similarly,Liao et al (2022) recently demonstrated that multiple SlPHR proteins play a role in the suppression of AM symbiosis by LP stress in tomato.It is, therefore, highly likely that SlPHL1 and other SlPHRs work together to regulate APase activity in a functionally redundant manner.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…The p-value for each comparison between the two data sets is displayed above the asterisk. The experiments were repeated three times with similar results.process of jasmonate-induced anthocyanin synthesis along with its homologs AtPHL1, AtPHL2, and AtPHL3(He et al, 2023). Similarly,Liao et al (2022) recently demonstrated that multiple SlPHR proteins play a role in the suppression of AM symbiosis by LP stress in tomato.It is, therefore, highly likely that SlPHL1 and other SlPHRs work together to regulate APase activity in a functionally redundant manner.…”
mentioning
confidence: 80%
“…Both AtPHR1 and AtPHL2 can directly regulate the transcriptional expression of AtPAP10 to enhance APase activity in response to LP stress (Sun et al, 2016). Also, AtPHR1 was thought to be a key regulator involved in the regulation of LP‐induced anthocyanin synthesis (Bustos et al, 2010; He et al, 2021; Liu et al, 2022), but it was recently discovered to be involved in the process of jasmonate‐induced anthocyanin synthesis along with its homologs AtPHL1, AtPHL2, and AtPHL3 (He et al, 2023). Similarly, Liao et al (2022) recently demonstrated that multiple SlPHR proteins play a role in the suppression of AM symbiosis by LP stress in tomato.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphate status and jasmonate signaling are intricately linked in plants. For example, jasmonate treatment stimulates PP-InsP synthesis ( 49 ), and PHR-activation enhances jasmonate production and signaling ( 50, 51 ). By manipulating intracellular PP-InsP levels, the Nudix effectors may influence jasmonate and auxin signaling in their host plants in addition to inducing starvation responses.…”
Section: Discussionmentioning
confidence: 99%
“…The plasmids were transformed into Agrobacterium tumefaciens strain GV3101 and injected into tobacco ( N. benthamiana ) leaves. As described previously (He et al, 2023; Li et al, 2023), YFP and 4,6-diamidino-2-phenylindole (DAPI) fluorescence of infected leaves were observed under a confocal laser scanning microscope (Olympus) after 48 h of co-expression. Primers used for cloning are listed in Supplemental Data Set 1.…”
Section: Methodsmentioning
confidence: 99%